Biweekly Raltitrexed Combined With Irinotecan as Second-Line Therapy for Patients With Metastatic Colorectal Cancer: A Phase II Trial. (5th February 2022) - Cheng, Ke; Zhou, Yu-Wen; Chen, Ye; Li, Zhi-Ping; Qiu, Meng; Liu, Ji-Yan
Objective: Irinotecan-based doublet chemotherapy strategy was standard second-line backbone for patients with oxaliplatin-refractory metastatic colorectal cancer. The aim of this study was to evaluate tolerability and efficacy of raltitrexed combined with irinotecan biweekly administered as the second-line therapy for mCRC patients. Methods: The study was a prospective, single-center, non-randomized, open-label phase II clinical trial. Patients with mCRC after failure with oxaliplatin and fluoropyrimidine or its derivatives were enrolled. Irinotecan (180 mg/m 2 ) and raltitrexed (2.5 mg/m 2 ) were given intravenously on day 1. Cycles were repeated every 2 weeks. The primary endpoint was progression-free survival (PFS), and the secondary endpoints included overall response rate (ORR), disease control rate (DCR), overall survival (OS), and adverse events (AEs). Results: Between December 2012 and October 2016, 33 and 35 patients enrolled were assessed for response and safety, respectively. The ORR was 8.6%, and the DCR was 71.4%. The median PFS was 4.5 months (95% CI 3.8-5.2). The median OS was 12.0 months (95% CI 8.5-15.5). Four patients received conversion therapy to no evidence of disease (NED), and 2 patients were still alive with beyond 24 months survival. The most common grade 3/4 AEs were anorexia (14.3%), vomiting (14.3%), nausea (11.4%), fatigue (8.6%), and leukopenia (8.6%). No one died from treatment-related events. The incidence and severity of toxicity were irrelevant to UGT1A1 status. Conclusions: The combination of irinotecan with raltitrexed is an efficient, convenient, and acceptable toxic regimen for second-line treatment for mCRC patients.